Closing the gap: a review of factors affecting quality improvement interventions at the primary care level - Zeelie, Andrea (Health Economics Unit, 2015)
Objective: The aim of this review is to analyse quality improvement interventions at the primary care level. Quality improvement interventions attempt to close the gap between clinical research and practice. The objectives of this review are to identify, synthesise and evaluate research literature relevant to primary care regarding quality improvement interventions; as well as identify the enabling and constraining factors impacting quality improvement at the primary care level. Design: This review involved a qualitative, systematic review of previously undertaken qualitative research. Data sources: Data was sourced from electronic databases PubMed and CINAHL. Study selection: Articles were selected based on their relevance and published in English in an academic journal between June 2001 and June 2011, using qualitative data collection and analysis methods to assess a quality improvement intervention at the primary care level. Data extraction: Data was extracted from the articles' 'findings' and 'discussion' sections. Data synthesis: 110 articles were identified, 11 of which were included. Thematic analysis occurred in three stages: line-by-line coding, creation of descriptive themes, and creation of analytical themes. Conclusion: Interventions aimed at quality improvement in primary care do not experience uniform ease of implementation. It is possible to create the conditions necessary for success by harnessing human capital; creating a nurturing, supportive and collaborative working environment; and providing inspirational leadership through management.